The Process of Performance Based Budgeting in Probolinggo City by Utilizing SIMRAL: A Phenomenology Study - Dipayana, Muhammad Avicinna; Triyuwono, Iwan; Andayani, Wuryan (Universitas Negeri Malang, 2017)
This study aims to interpret the performance-based budgeting process by utilizing Planning, Budgeting and Reporting Information System (SIMRAL) in Probolinggo Cityâs budget. This research is regarded as qualitative, particularly referring to phenomenological study projected to dig deep into the informantsâ perspectives and their meaning. The results of this study revealed that the performance-based budgeting process in Probolinggo City with SIMRALâs utilization is interpreted the disobedience of budgeting to planning; moreover, SIMRAL is regarded as a solution for such disobedience. Referring to such a notion, a conclusion can be drawn which reads